Inferring the Diets of Extinct Giant Lemurs from Osteological Correlates of Muscle Dimensions. Issue 2 (13th January 2018) - Perry, Jonathan M. G.
ABSTRACT: The jaw adductor muscles of extinct mammals are often reconstructed to elucidate paleoecological relationships and to make broad comparisons among taxa. Muscle lever arms, bite load arms, muscle dimensions, and gape are often also reconstructed to better understand feeding. Several different approaches to these and related goals are discussed here. A protocol for reconstructing muscle dimensions and bite force using biomechanically informative skull measurements and osteological proxies of muscle dimensions is described and applied to a case study of subfossil Malagasy lemurs. The results of this case study show that most subfossil lemurs emphasized the masseter and medial pterygoid muscles over the temporalis. This supports the inference that these extinct lemurs depended heavily on tough food like leaves. Exceptions include signals of hard‐object feeding in Archaeolemur that vary between A. majori and A. edwardsi . Reconstructions of soft‐tissue and function are important for understanding past ecological relationships. Even those based on well‐supported osteological proxies from extant analogues have limitations for making precise inferences. Anat Rec, 301:343–362, 2018. © 2018 Wiley Periodicals, Inc.